The prevalence of post traumatic and associated factors among nurses during COVID_19 pandemics: a systematic review and meta-analysis - Afsaneh Karbasi; Masoudeh Babakhanian; Akram Ahmadzadeh; Victoria Omranifard (BMC Psychology, 2024)
Abstract Background Despite the negative outcomes, exposure to a crisis may cause people to experience positive changes. This study aims to analyze the prevalence of post-traumatic growth (PTG) and its relevant factors among nurses during the COVID-19 pandemic. Method The research protocol was registered with PROSPERO (CRD42022329671), and PRISMA steps were taken in this study. PubMed, Scopus and ProQuest were explored on 1/9/2022 to create the research database. According to the inclusion criterion, all studies analyzing the prevalence of post-traumatic growth through the PTG Inventory were considered eligible. They were all qualitatively assessed through the modified version of the Quality Assessment Checklist for prevalence studies. Results A total of 15 papers met the inclusion criterion (n = 22756). According to the research results, the prevalence of PTG was randomly calculated ES [95% Conf. Interval = 0.15 [0.12–0.17]), and heterogeneity was reported I2 = 98.52% (P = 0.000). The results also indicated that the mean score of PTGI decreased in nurses as their work experience and mean age increased. However, the effect was not statistically significant for the mean age (P = 0.06). According to the results, the PTGI score decreased in nurses with more work experience, a finding which was statistically significant (P = 0.04). Conclusion This meta-analysis determined a 15% prevalence rate of PTG in nurses. Psychological interventions should be developed and applied to older nurses with more work experience in order to mitigate the harm caused by the pandemic and its consequent crises.